(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted at the Animal Production Field/ College of Agriculture and Forestry / University of Mosul for the period from (1/2/2023) to (1/5/2023) 20 weaning age lambs were used (three months) lambs were divided into four groups (coefficients) The first group (T1) five Awassi lambs from Awassi parents weighed (24.82 ± 2.62) and the second (T2) five crossing lambs (Hamdani × Awassi) average weight ( 23.20 ± 2.43) The two groups were fed a diet containing high degraded soybean meal, while the third group (T3) was five Awassi lambs from Awassi parents with average weight (23.42± 2.53) and the fourth group (T4) five crossing lambs (Hamdani ×Awassi) average weight (24.33± 2.78) and the two groups were fed a diet containing low-degradation soybean meal. It was noted from the results of the study that the feed intake was close between the treatments and amounted to (1149.44) kg / day. Total gain in T4 increased (24.23) kg as compared to the first, second and third (18.22, 21.90, 19.52) kg respectively, this was reflected in increse of the final weight, (48.56) kg and the empty body (44.06) kg (P? 0.05) were achieved in T4 as compared other treatmants, salthough we find that the differences in the weight of the carcass did not reach the level of significant and the differences were highest in T4, followed by T2, T1 and T3, (22.41, 21.59, 21.55, 20.18) kg respectively. On the other hand, it is noted that dressing percentage 50% and the area rib eye 19.12cm2 was better in the sighnificantly lambs in T1 fed on a highly degraded soybeam mal compared to the lambs T1, T3 and T4 (47.99, 47.60, 46.17)% (17.68, 17.68, 16.83 cm2) respectively.